IMPLICATIONS OF CO-CURRICULAR ACTIVITIES ON QUALITY EDUCATION IN PUBLIC SECONDARY SCHOOLS IN KENYA - Omae, Nelson Siocha; Onderi, Henry Nyabuto; Mwebi, Benard (Advances in Social Sciences Research Journal, 2017)
The purpose of the study was to explore implications of co-curricular activities on quality education in public secondary schools in Kisii County, Kenya. The objective of the study was to establish the impact of co-curricular activities on quality education. This study employed the Production Function Theory and adopted sequential explanatory design . Population o f study consisted of 9 education officers, 334 principals and 334 senior teachers. Stratified sampling technique was used to select 181 principals and 181 senior teachers while saturated sampling was used to select nine education officers. Krescie and Morgan ’ s formula was used to obtain the sample size . Instruments for data collection were two questionnaires, an interview schedule and a document analysis guide. Reliability was done by piloting in 34 schools through the split-half method. The reliability index for the instruments was 0.826. The validity was done by expert judgment and by making them simple. The quantitative data was analyzed using descriptive and inferential statistics. The qualitative data was analyzed using thematic analysis. It was concluded that CCA facilities are inadequate, have not attained perfect utilization because of low emphasis, inadequate monitoring and supervision by teachers. This study will help all education stakeholders make decisions regarding implemention of policies that ensure provision of CCA for quality education. The researcher recommends that the Ministry of Education and schools revisit their policies related to the provision of CCA for quality education and work towards their implementation